Rynek usług turystycznych a rynek pracy w Polsce – ujęcie wielowymiarowe - Stefan Bosiacki; Magdalena Jakubowska (Ekonomiczne Problemy Turystyki, 2015)
The research problem underlying the article was the relation between tourism industry and the labor market at the local level across the whole country. Therefore, the main objective was to determine this relation in Poland. The current research methodologies on tourism and labor market provide data for the whole country (such as tourism satellite account TSA) or only to specific areas and there are the case studies. The results from the article may be useful to develop a strategy for selected divisions of the country.